2023
DOI: 10.1161/circresaha.122.321228
|View full text |Cite
|
Sign up to set email alerts
|

Smooth Muscle Mineralocorticoid Receptor Promotes Hypertension After Preeclampsia

Abstract: BACKGROUND: Preeclampsia is a syndrome of high blood pressure (BP) with end organ damage in late pregnancy that is associated with high circulating soluble VEGF receptor (sFlt1 [soluble Fms-like tyrosine kinase 1]). Women exposed to preeclampsia have a substantially increased risk of hypertension after pregnancy, but the mechanism remains unknown, leaving a missed interventional opportunity. After preeclampsia, women have enhanced sensitivity to hypertensive stress. Since smooth muscle cell mineral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 72 publications
(107 reference statements)
0
18
0
Order By: Relevance
“…231 Furthermore, we have also recently demonstrated that sFlt-1-induced vascular injury in pregnancy produces enhanced sensitivity of smooth muscle cell-mineralocorticoid receptor, contributing to post-partum hypertension in response to common stressors such as salt. 232 Taken together, these data suggest that exposure to high levels of sFlt-1 during pregnancy reprograms the cardiovascular system to "remember" the initial insult and respond accordingly. In this model, it is presumed that this effect is independent of pre-existing cardiovascular risk factors.…”
Section: Diseasesmentioning
confidence: 85%
“…231 Furthermore, we have also recently demonstrated that sFlt-1-induced vascular injury in pregnancy produces enhanced sensitivity of smooth muscle cell-mineralocorticoid receptor, contributing to post-partum hypertension in response to common stressors such as salt. 232 Taken together, these data suggest that exposure to high levels of sFlt-1 during pregnancy reprograms the cardiovascular system to "remember" the initial insult and respond accordingly. In this model, it is presumed that this effect is independent of pre-existing cardiovascular risk factors.…”
Section: Diseasesmentioning
confidence: 85%
“…The primary function of aldosterone, via mineralocorticoid receptor (MR), is to regulate salt and water homeostasis in the body by acting on the distal tubule and collecting duct of nephrons in the kidney, which in turn leads to sodium and water reabsorption and potassium excretion 1,4,5 . However, MR are expressed in different cell types including vascular smooth muscle cells (VSMC) 6 , endothelial cells 9 , adipocytes that form perivascular adipose tissue 7 , and immune cells 8,9 , where aldosterone can exert its deleterious effects including inflammation, oxidative stress, accelerated fibrosis, and proliferation 4,5,8,[10][11][12][13] . In this context, hyperaldosteronism and hyperactivation of MR signaling are key features in the pathogenesis of diabetes 2,3,10 , obesity 2,3,10 , atherosclerosis 14 , stroke 13 , and hypertension 15 .…”
Section: Introductionmentioning
confidence: 99%
“…21,[26][27][28] Using the sFlt1-induced preeclampsia model in C57Bl/6 mice during pregnancy, we have demonstrated that high circulating sFlt1 results in increased blood pressure and kidney damage in late pregnancy, and the high sFlt1 and resulting syndrome all normalize postpartum, consistent with the human phenotype. 29 Several months postpartum, mice with prior preeclampsia have an increased blood pressure response to high salt intake and enhanced vascular remodeling in response to injury. 29,30 These findings suggest persistent changes, making the vasculature more susceptible to dysfunction even after preeclampsia is resolved.…”
mentioning
confidence: 99%
“…29 Several months postpartum, mice with prior preeclampsia have an increased blood pressure response to high salt intake and enhanced vascular remodeling in response to injury. 29,30 These findings suggest persistent changes, making the vasculature more susceptible to dysfunction even after preeclampsia is resolved.…”
mentioning
confidence: 99%
See 1 more Smart Citation